2019
DOI: 10.1038/s41467-019-09361-0
|View full text |Cite
|
Sign up to set email alerts
|

The parasitic worm product ES-62 normalises the gut microbiota bone marrow axis in inflammatory arthritis

Abstract: The human immune system has evolved in the context of our colonisation by bacteria, viruses, fungi and parasitic helminths. Reflecting this, the rapid eradication of pathogens appears to have resulted in reduced microbiome diversity and generation of chronically activated immune systems, presaging the recent rise of allergic, autoimmune and metabolic disorders. Certainly, gastrointestinal helminths can protect against gut and lung mucosa inflammatory conditions by modulating the microbiome and suppressing the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 78 publications
7
84
0
Order By: Relevance
“…Changes in the microbiome contribute to the loss of intestinal barrier integrity 46,47,58 during ageing and impact directly on obesity and longevity 48,49 . We have recently shown that the protection afforded by ES-62 against inflammatory arthritis is associated with normalisation of the gut microbiome and stabilisation of gut barrier integrity that prevents generation of pathogenic TH17-mediated inflammation and allows homeostatic resolution of inflammation by IL-10 + Bregs in the collageninduced arthritis model of rheumatoid arthritis in male mice 16 . Thus, we investigated whether ES-62 acted to normalise the ageing microbiota and prevent the dysbiosis resulting in loss of barrier integrity by metagenomic analysis of faecal (ileum plus colon) material, with samples from individual mice pooled to generate a representative cohort phenotype.…”
Section: Es-62 Maintains Gut Microbiota Homeostasis During Hcd-inducementioning
confidence: 99%
See 2 more Smart Citations
“…Changes in the microbiome contribute to the loss of intestinal barrier integrity 46,47,58 during ageing and impact directly on obesity and longevity 48,49 . We have recently shown that the protection afforded by ES-62 against inflammatory arthritis is associated with normalisation of the gut microbiome and stabilisation of gut barrier integrity that prevents generation of pathogenic TH17-mediated inflammation and allows homeostatic resolution of inflammation by IL-10 + Bregs in the collageninduced arthritis model of rheumatoid arthritis in male mice 16 . Thus, we investigated whether ES-62 acted to normalise the ageing microbiota and prevent the dysbiosis resulting in loss of barrier integrity by metagenomic analysis of faecal (ileum plus colon) material, with samples from individual mice pooled to generate a representative cohort phenotype.…”
Section: Es-62 Maintains Gut Microbiota Homeostasis During Hcd-inducementioning
confidence: 99%
“…Paraffin embedded tissues were sectioned at 5-6 µm and OCT tissues were cryosectioned (Thermoscientific, UK) at 8-10 µm thickness between -14 to -30°C. All tissues were haematoxylin and eosin (H&E) stained, gut and liver tissue sections were also stained with Gömöri's Trichrome using previously described methods 16 .…”
Section: Tissue Processing Histology and Immunofluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that a single, defined ES protein, ES-62, can resolve chronic inflammation by normalising aberrant MyD88 signalling to homeostatically restore immunoregulation, irrespective of the inflammatory phenotype [4,5,[10][11][12]. MyD88 is increasingly recognized not only as a key innate immune system receptor transducer but also as an integrator of dysregulated inflammatory and metabolic pathways [7,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Critically, these HCD-TLR4/ MyD88-induced effects are exacerbated by ageing [18]. Thus, based on ES-62's targeting of MyD88 and demonstrable ability to protect against chronic inflammatory allergic and autoimmune conditions [4,5,[10][11][12], we investigated whether it could safeguard against the impact of HCD-associated ageing in C57BL/6J mice. Our approach of combining longitudinal (survival) and cross-sectional (intervention) studies has revealed that ES-62 improves healthspan in both male and female HCD-fed mice and substantially extends median lifespan of male HCD-fed mice.…”
Section: Introductionmentioning
confidence: 99%